Iron Metabolism and Immune Regulation - Ni, Shuo; Yuan, Yin; Kuang, Yanbin; Li, Xiaolin (Frontiers in Immunology, 2022)
Abstract Iron is a critical element for living cells in terrestrial life. Although iron metabolism is strictly controlled in the body, disturbance of iron homeostasis under certain type of condition leads to innate and adaptive immune response. In innate immunity, iron regulates macrophage polarizations, neutrophils recruitment as well as NK cells activity. In adaptive immunity, iron had an effect on the activation and differentiation of Th1, Th2 and Th17 and CTL, as well as antibody response in B cells. In this review, we focused on iron and immune regulation, and listed the specific role of iron in macrophage polarization, T cell activation and B cells antibody response. In addition, the correlation and some therapeutic strategies targeting iron in cancer are also discussed.